Long working hours and health in Europe: Gender and welfare state differences in a context of economic crisis. (July 2016) - Artazcoz, Lucía; Cortès, Imma; Benavides, Fernando G.; Escribà-Agüir, Vicenta; Bartoll, Xavier; Vargas, Hernán; Borrell, Carme
Abstract: This article examines the relationship between moderately long working hours and health status in Europe. A cross-sectional study based on data from the 2010 European Working Conditions Survey (13, 518 men and 9381 women) was performed. Working moderately long hours was consistently associated with poor health status and poor psychological wellbeing in countries with traditional family models, in both sexes in Liberal countries and primarily among women in Continental and Southern European countries. A combination of economic vulnerability, increasing labour market deregulation and work overload related to the combination of job and domestic work could explain these findings. Highlights: Contradictory results in studies about moderately long work hours and health. Need of conceptual frameworks taking into account the role of choice. Individual and contextual factors related to choice shape the association. The relationship of long hours and health differs by gender and welfare state regimes.